Kinetics and thermodynamic analysis of maize cob pyrolysis for its bioenergy potential using thermogravimetric analyzer - Gupta G.K.; Mondal M.K. (My University, 2025)
The purpose of the study was to inspect the thermal degradation behavior of maize cob to find out its pyrolytic behavior for bioenergy generation. Prior to thermal degradation, the initial characterizations (proximate analysis, ultimate analysis and HHV) were done to check its suitability toward pyrolysis process. Later, thermogravimetric experiments were performed from ambient temperature to 900 °C at three different slow heating rates (5, 10 and 20 °C min−1) in a thermogravimetric analyzer with inert atmosphere. Thermogravimetric results confirmed that maximum devolatilization occurred at the temperature range of 200–460 °C. For kinetic and thermodynamic studies, four iso-conversional models (Friedman, FWO, KAS and Starink) were applied and average activation energies calculated from these models were 197.63, 186.06, 185.39 and 185.80 kJ mol−1, respectively. The potential energy barrier between activation energy and enthalpy of reaction (~ 4–6 kJ mol−1) revealed the favorable conditions for product formation. Gibbs free energy change (ΔG) for maize cob was found in the range of 174.91 to 179.47 kJ mol−1 and 174.27 to 180.23 kJ mol−1 for KAS and Friedman methods, respectively. Thus, kinetic and thermodynamic data along with HHV (15.27 MJ kg−1) showed that maize cob had enough potential to be utilized for bioenergy production. © 2019, Akadémiai Kiadó, Budapest, Hungary.